Colombia : First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the First Review Under the Stand-By Arrangement for Colombia. Under the authorities' program, economic performance has been mostly favorable. Real economic growth appears to be recovering, led by a pickup in domestic demand that outweighed a decline in net exports. Inflation, however, has remained above the program target. Since late February, the currency has appreciated, responding partly to a sharp decline in the country risk premium. The program is on track and the authorities have reiterated their full commitment to achieving the main elements of the program's macroeconomic framework.